Heat dissipation and fatigue crack kinetic features of titanium alloy Grade 2 after laser shock peening - Anastasia Iziumova; Aleksei Vshivkov; Aleksandr Prokhorov; Elena Gachegova; Denis Davydov (Fracture and Structural Integrity)
The work is devoted to experimental investigation of the laser shock peening (LSP) effect on fatigue crack propagation rate and heat dissipation at the crack tip in specimens made of titanium alloy Grade 2 with a stress concentrator. It is shown that the LSP can leads both to positive and negative effect on fatigue lifetime. The effective processing scheme, which includes stress concentrator zone, was proposed. This type of treatment forms an optimal residual stress field, which slows down the crack initiation and propagation processes. The effective LSP processing scheme reduces the value of the stress intensity factor and, as a consequence, effects on an intensity of plastic deformation at the crack tip. This effect can be visualised by measurement of heat flux from the crack tip area. Both heat flux from the crack tip and crack rate are less in the LSP processed specimens. Structural investigations of LSP treated material near fatigue crack path have shown that structural defects (twins) that appear on the surface of the material as a result of LSP do not have a significant effect on the fatigue crack propagation, and the configuration of the residual stresses field created by LSP plays a decisive role.